RYR1-related congenital myopathy with fatigable weakness, responding to pyridostigimine. - Illingworth, M; Main, M; Pitt, M; Feng, L; Sewry, C; Gunny, R; Vorstman, E; Beeson, D; Manzur, A; Muntoni, F; Robb, SA (2014)
The spectrum of RYR1 mutation associated disease encompasses congenital myopathies, exercise induced rhabdomyolysis, malignant hyperthermia susceptibility and King-Denborough syndrome. We report the clinical phenotype of two siblings who presented in infancy with hypotonia and striking fatigable ptosis. Their response to pyridostigimine was striking, but genetic screening for congenital myasthenic syndromes was negative, prompting further evaluation. Muscle MRI was abnormal with a selective pattern of involvement evocative of RYR1-related myopathy. This directed sequencing of the RYR1 gene, which revealed two heterozygous c.6721C>T (p.Arg2241X) nonsense mutations and novel c.8888T>C (p.Leu2963Pro) mutations in both siblings. These cases broaden the RYR1-related disease spectrum to include a myasthenic-like phenotype, including partial response to pyridostigimine. RYR1-related myopathy should be considered in the presence of fatigable weakness especially if muscle imaging demonstrates structural abnormalities. Single fibre electromyography can also be helpful in cases like this.